Mind games [computer game AI]. - Cass, S.
An increasing number of other games are taking advantage of changes in computer architecture and the growth in processing power to become smarter than ever before. Although most of these games use relatively unsubtle AI techniques, a few pioneers are even showing the academic AI community a trick or two. While AI originated in the laboratory, it has now been coopted by designers of video games, and work is under way on increasing the learning powers of a video games cast of characters and refining their social interactions with one another and with human players, too. At this point, even cinematographers and the military are showing interest in possible applications. To beat the competition, video games are getting smarter. Game AIs have two big advantages over their academic counterparts-they can cheat, and they can get a lot of help from the world they find themselves in.
Keywords: AI; Academic AI community; Artifical intelligence; Cheating; Computer architecture; Computer game; Human players; Social interactions refinement; Video games